From leaf to continent: The multi-scale distribution of an invasive cryptic pathogen complex on oak. (December 2018) - Desprez-Loustau, Marie-Laure; Massot, Marie; Toïgo, Maude; Fort, Tania; Aday Kaya, Ayse Gülden; Boberg, Johanna; Braun, Uwe; Capdevielle, Xavier; Cech, Thomas; Chandelier, Anne; Christova, Petya; Corcobado, Tamara; et al.
Abstract: The spatial distribution and niche differentiation of three closely related species ( Erysiphe alphitoides, Erysiphe quercicola and Erysiphe hypophylla ) causing oak powdery mildew was studied at scales ranging from the European continent, where they are invasive, to a single leaf. While E. alphitoides was dominant at all scales, E. quercicola and E. hypophylla had restricted geographic, stand and leaf distributions. The large-scale distributions were likely explained by climatic factors and species environmental tolerances, with E. quercicola being more frequent in warmer climates and E. hypophylla in colder climates. The extensive sampling and molecular analyses revealed the cryptic invasion of E. quercicola in nine countries from which it had not previously been recorded. The presence of the three species was also strongly affected by host factors, such as oak species and developmental stage. Segregation patterns between Erysiphe species were observed at the leaf scale, between and within leaf surfaces, suggesting competitive effects. Highlights: First report of Erysiphe quercicola in Armenia, Bulgaria, Hungary, Iran, Israel, Portugal, Slovakia, Sweden, Turkey. The occurrence of E. quercicola is associated with higher winter temperatures in Europe. Sampling the most obvious symptoms may induce a bias, as shown for E. hypophylla . Seedlings harbour different Erysiphe communities than the canopy of mature trees. Cryptic species vary in their spatial distribution and ecology within the pathogen complex.